2004
DOI: 10.1007/s00432-003-0538-3
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of E2F1 associated with LOH at RB locus and hyperphosphorylation of RB in non-small cell lung carcinoma

Abstract: Our results suggest that overexpression of E2F1, induced both by LOH at the RB locus and anomalous phosphorylation of the RB protein, is involved in the development of non-small cell lung carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…68 We previously showed that E2F1 is overexpressed in SCLC while it is undetectable in NSCLC as compared to corresponding normal lung, thereby identifying a differential pattern of E2F1 protein expression in lung tumors. 69 By contrast, other studies have reported amplification of the E2F1 gene locus at 20q11.2, 70 as well as increased E2F1 protein level in NSCLC, [71][72][73][74] and have shown that E2F1 is an adverse prognostic factor in these tumors. 71 The reasons of such discrepancies remain unknown.…”
Section: Alteration Of the Components Of G 2 And M Phases In Lung Tumorsmentioning
confidence: 72%
See 1 more Smart Citation
“…68 We previously showed that E2F1 is overexpressed in SCLC while it is undetectable in NSCLC as compared to corresponding normal lung, thereby identifying a differential pattern of E2F1 protein expression in lung tumors. 69 By contrast, other studies have reported amplification of the E2F1 gene locus at 20q11.2, 70 as well as increased E2F1 protein level in NSCLC, [71][72][73][74] and have shown that E2F1 is an adverse prognostic factor in these tumors. 71 The reasons of such discrepancies remain unknown.…”
Section: Alteration Of the Components Of G 2 And M Phases In Lung Tumorsmentioning
confidence: 72%
“…72 Amplification of the E2F2 gene locus at 1p36 has also been observed in SCLC 75 and increased expression of E2F3 protein has been found in NSCLC and SCLC. 74 Overall, these studies indicate that E2F factors likely contribute to lung carcinogenesis. However, as E2Fs and notably E2F1 have multiple biological functions, it remains to determine whether each protein contributes to lung tumorigenesis only through deregulation of cell cycle progression, or extands beyond the framework of RB and cell cycle control.…”
Section: Alteration Of the Components Of G 2 And M Phases In Lung Tumorsmentioning
confidence: 99%
“…In previous studies, E2F1 was shown to promote breast cancer cell and hepatocarcinoma cell proliferation, and conferred antiestrogen resistance to breast cancer cells (Arakawa et al, 2004;Louie et al, 2004). Transgenic models with E2F1 overexpression (Lee et al, 2004) and clinical data from patients with different types of cancer (Gorgoulis et al, 2002;Yamazaki et al, 2003;Imai et al, 2004;Lee et al, 2004;Onda et al, 2004) have further supported the role of E2F1 in oncogenesis. Under normal circumstances, E2F1 gene expression is tightly regulated, and its protein product is rapidly degraded.…”
Section: Discussionmentioning
confidence: 94%
“…The main substrates of CDK activation are the Rb protein family (pRb, p107, and p103) and E2F (Imai et al, 2004). Li et al explored the role of antisense RNA gene therapy in targeting cyclin D1 in lung cancer, and they found that knockingdown cyclin D1 can induce apoptosis in A549 cells, which may be associated with the reduced expression of intracellular pRb, E2F1, VEGF, MMP-2, and MMP-9 (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%